Castrum Bene 15 : a castle as a status symbol : 15th International Castellological Conference : book of abstracts and study tour guide = Burg als Statussymbol : 15. Internationale Konferenz für Burgenforschung : Zusammenfassungen der Vorträge und Studienfahrtführer = Zamek jako symbol statusu : 15. Międzynarodowa Konferencja Kastellologiczna : księga abstraktów i opis wyjazdu studyjnego, Zamek Książ, 16.05.-19.05.2017 - Boguszewicz, Artur; Radziszewska, Janina; Madejski, Bartłomiej; Murczkiewicz, Janusz (Uniwersytet Wrocławski, 2017)
The publication is a collection of abstracts of the papers presented during the 15th International Conference Castrum Bene: “A castle as a status symbol” organised by the University of Wroclaw. The conference was dedicated to the memory of the Professor Leszek Kajzer (1944-2016), a member of the Permanent Committee of Castrum Bene for many years. The authors of the papers were researching not only the military, political, economic and residential purposes of erecting castles but also their symbolic capital, the analysis of which requires research tools employed by archaeology, architecture, history and history of art.
Keywords: archeology; architecture; castles; Castrum Bene; Central Europe; early modern period; material culture; middle ages; status symbol